PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN JOB BURNOUT TERHADAP KINERJA KARYAWAN KONSTRUKSI PADA PT. WIDY KENCANA JAYA KUALA TANJUNG, SUMATERA UTARA - Putri Sandrina Sitompul; Riza Indriani (STKIP Subang, 2026)
The construction industry is characterized by high occupational risks, where employees simultaneously face physical hazards on-site and psychological pressure due to project deadlines. Two factors considered to have significant influence in this context are Occupational Health and Safety (OHS) and Job Burnout. This study aims to analyze the influence of OHS and Job Burnout on the performance of construction employees at PT. Widy Kencana Jaya, Kuala Tanjung, North Sumatra, both partially and simultaneously. The study employs a quantitative approach with a causal associative research design. The population and sample consist of all 56 construction employees of PT. Widy Kencana Jaya, selected using saturated sampling technique. Data were collected through a Likert scale 1–5 questionnaire, field observations, and interviews. Instrument tests include validity using Pearson Product Moment correlation (r table = 0.361) and Cronbach's Alpha reliability, all of which were declared valid and reliable. Classical assumption tests include Kolmogorov-Smirnov normality test, multicollinearity test (Tolerance & VIF), and heteroscedasticity test (Scatterplot). Multiple linear regression analysis using SPSS 26.0 For Windows yielded the equation Y = 29.709 + 0.449X₁ – 0.528X₂ + e. Results show that: (1) OHS has a positive and significant effect on employee performance (t-count = 4.704 > t-table = 2.006; sig. = 0.000 < 0.05), thus H₁ is accepted; (2) Job Burnout has a negative and significant effect on employee performance (t-count = 4.508 > t-table = 2.006; sig. = 0.000 < 0.05), thus H₂ is accepted; (3) Simultaneously, OHS and Job Burnout significantly influence employee performance (F-count = 53.300 > F-table = 3.172; sig. = 0.000 < 0.05) with Adjusted R² = 0.655, indicating that both variables explain 65.5% of the variation in employee performance, thus H₃ is accepted. These findings imply that improving employee performance in the construction sector requires an integrated approach that strengthens OHS management systems while simultaneously managing employees' psychological conditions to prevent burnout.